MENINGKATKAN PROFITABILITAS MELALUI OPTIMALISASI MARGIN LABA DAN PEMBERIAN KREDIT SERTA MENURUNKAN BIAYA OPERASIONAL PADA PERUSAHAAN PERBANKAN PERSERO - Sarmigi, Elex; Wahyuni, Endah Sri; Sumanti, Eva; Bustami, Bustami; Azhar, Azhar (Program Studi Akuntansi | Fakultas Ekonomi dan Bisnis | Universitas Komputer Indonesia, 2025)
Profitability is a crucial component for a company to remain competitive, grow, and deliver value to shareholders. To achieve maximum profitability, the company must be able to increase profit margins and liquidity while reducing operational costs. This study aims to analyze the impact of the Operating Expenses to Operating Income Ratio (BOPO), Loan-to-Deposit ratio (LDR), and Net Interest Margin (NIM) on Return on Assets (ROA) for state-owned banking companies listed in the Financial Services Authority (OJK) from 2018 to 2023. This research also examines the mediating role of NIM in the relationship between BOPO, LDR, and ROA. The data used in this study were obtained from the annual reports of banks listed in OJK, employing the Structural Equation Model (SEM). The results show that BOPO has a significant negative effect on ROA, LDR has a significant positive effect on ROA, and NIM has a significant positive effect on ROA. Furthermore, NIM plays a partial mediating role in the relationship between BOPO and ROA, but it does not mediate the relationship between LDR and ROA. These findings provide insights for bank management to focus on operational efficiency and effective NIM management to improve profitability.